Pengaruh Brand Image, Promosi dan Biaya Pendidikan Terhadap Keputusan Mahasiswa Melanjutkan Studi Pada Program Studi Pendidikan Ekonomi - Murti, Tri Kresna (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Consumer decision, which is assumed as a student decision is one of the important factors for the existence of college. In this study there is variable cost of education which is one component of instrumental input that is very important in the implementation of education. It can be said that the educational process will not work without cost support. The second variable is promotion can be interpreted as a flow of information persuasion made to direct a person or organization to action to create exchange within the company. And other variables are brand image formed from how the company perform its operational activities, which has a main foundation in terms of service. This is a quantitative research method. Data collection was carried out questioner, Test of validity of instrument was using Product Moment correlation, Hypothesis test used of simple regression. Research results: (1) Have a positive and significant brand image to Interest university student making decision continues study in economics education programs. (2) Have a positive and significant promotion interest university student making decision continues study in economics education programs. (3) Have a positive and significant costs study interest university student making decision continues study in economics education programs.